Canons 1692 §§1-2; 1151; 1152; and 1153: Response to Questions Posed by a Bishop Regarding the Need for Bishop to Give Permission for a Baptized Catholic to Initiate a Civil Divorce - Ecclesia Catholica Pontificium Consilium de Legum Textibus; Coccopalmerio, Francesco 1938- (2021)
A member of the Canon Law Society of America requested that this 2015 letter from the Pontifical Council for Legislative Texts be published herein since it was not published by the Society in the year in which it was issued. In recent years, several US tribunals have dealt with the question addressed by the Council, and it was noted that having a printed source to cite when responding to inquiries from the Christian Faithful will make the letter more accessible.